Identifying subgroups and risk among frequent emergency department users in British Columbia. Issue 1 (2nd January 2021) - Moe, Jessica; O'Sullivan, Fiona; McGregor, Margaret J.; Schull, Michael J.; Dong, Kathryn; Holroyd, Brian R.; Grafstein, Eric; Hohl, Corinne M.; Trimble, Johanna; McGrail, Kimberlyn M.
Abstract: Objective : Frequent emergency department (ED) users are heterogeneous. We aimed to identify subgroups and assess their mortality. Methods : We identified patients ≥18 years with ≥1 ED visit in British Columbia from April 1, 2012 to March 31, 2015, and linked to hospitalization, physician billing, prescription, and mortality data. Frequent users were the top 10% of patients by ED visits. We employed cluster analysis to identify frequent user subgroups. We assessed 365‐day mortality using Kaplan‐Meier curves and conducted Cox regressions to assess mortality risk factors within subgroups. Results : We identified 4 subgroups. Subgroup 1 ("Elderly") had median age 77 years (interquartile range [IQR]: 66–85), 5 visits/year (IQR: 4–6), median 8 prescription medications (IQR: 5–11), and 24.7% mortality. Subgroup 2 ("Mental Health and Alcohol Use") had median age 48 years (IQR: 34–61), 13 visits/year (IQR: 10–16), and 12.3% mortality. They made a median 31 general practitioner visits (IQR: 19–51); however, only 23.7% received a majority of services from 1 primary care physician. Subgroup 3 ("Young Mental Health") had median age 39 years (IQR: 28–51), 5 visits/year (IQR: 4–6), and 2.2% mortality. Subgroup 4 ("Short‐term") had median age 50 years (IQR: 34–65), 4 visits/year (IQR: 4–5) regularly spaced over a short term, and 1.4% mortality. Male sex (all subgroups), long‐term care ("Mental Health and Alcohol Use;" "Young Mental Health"), and rural residence ("Elderly" in long‐term care; "Young Mental Health") were associated with increased mortality. Conclusions : Our results identify frequent user subgroups with varying mortality. Future research should explore subgroups' unmet needs and tailor interventions toward them.